THE OPTIMIZATION OF A RESONANT TWO-INDUCTOR BOOST CELL FOR A PHOTOVOLTAIC MODULE INTEGRATED CONVERTER - Li, Q.; Wolfs, Peter (University of Queensland, 2004)
This paper studies the optimization of a resonant two-inductor boost cell for a photovoltaic (PV) Module Integrated Converter (MIC). The resonant two-inductor boost cell is current fed from a two-phase buck converter and produces a rectified sinusoidal output voltage that is applied to an unfolding stage. This paper concentrates on resonant parameter selection to achieve the lowest power loss. The resonant two-inductor boost cell also employs a resonant gate drive, which minimizes the gate drive power and further improves the converter overall efficiency. The experimental results of a 1 MHz converter with an average power of 50 W are provided.